A hybrid linear actuator based on screw clamp operation principle: Design and experimental verification. (August 2022) - Shi, Yunlai; Sun, Haichao; Cheng, Dingji; Zhang, Jun; Lin, Yuyang; Sun, Han
This paper presents a hybrid linear actuator using screw clamp operation principle. The actuator mainly consists of a hollow electromagnetic torque motor located between two clamping nuts, two hollow cylindrical shaped piezoelectric stacks symmetrically configured at two ends of the actuator and a feed-screw (also considered as the mover of the actuator) assembled throughout all the parts. The torque motor is symmetrically connected to two clamping nuts via two torsion coupling springs located at either end of the motor spindle. Two piezoelectric stacks can work independently to propel the opposing loads, which effectively take advantage of the anti-compression and non-tensile characteristics of piezoelectric element. The special feature of the actuator is the screw clamp mechanism, the operation of which involves intermittent rotation of two nuts (driven by the torque motor) on a feed-screw to achieve the bi-direction piezoelectric motion accumulation. Furthermore, the application of feed-screw could decrease the actuator's sensitivity to wear, in order to realize a rigid self-locking and thus ensure the actuator's holding capacity. A prototype was fabricated and the experimental results show that the no-load speed, maximum thrust, and peak power of the actuator were 20 mm/s, 280 N, and 1.54 W, respectively.